Spatiotemporal Features of Coastal Waters in Southwest Finland - Suominen, Tapio (fi=Turun yliopisto|en=University of Turku|, 2015)
In coastal waters, physico-chemical and biological properties and constituents vary at different time scales. In the study area of this thesis, within the Archipelago Sea in the northern Baltic Sea, seasonal cycles of light and temperature set preconditions for intra-annual variations, but developments at other temporal scales occur as well. Weather-induced runoffs and currents may alter water properties over the short term, and the consequences over time of eutrophication and global changes are to a degree unpredictable. The dynamic characteristics of northern Baltic Sea waters are further diversified at the archipelago coasts. Water properties may differ in adjacent basins, which are separated by island and underwater thresholds limiting water exchange, making the area not only a mosaic of islands but also one of water masses. Long-term monitoring and in situ observations provide an essential data reserve for coastal management and research. Since the seasonal amplitudes of water properties are so high, inter-annual comparisons of water-quality variables have to be based on observations sampled at the same time each year. In this thesis I compare areas by their temporal characteristics, using both inter-annual and seasonal data. After comparing spatial differences in seasonal cycles, I conclude that spatial comparisons and temporal generalizations have to be made with caution. In classifying areas by the state of their waters, the results may be biased even if the sampling is annually simultaneous, since the dynamics of water properties may vary according to the area. The most comprehensive view of the spatiotemporal dynamics of water properties would be achieved by means of comparisons with data consisting of multiple annual samples. For practical reasons, this cannot be achieved with conventional in situ sampling. A holistic understanding of the spatiotemporal features of the water properties of the Archipelago Sea will have to be based on the application of multiple methods, complementing each other’s spatial and temporal coverage. The integration of multi-source observational data and time-series analysis may be methodologically challenging, but it will yield new information as to the spatiotemporal regime of the Archipelago Sea.

Rannikkovesien fysikaalis-kemialliset ja biologiset ominaisuudet vaihtelevat eri ajanjaksoissa. Saaristomerellä veden ominaisuuksia ja aineiden kiertoa säätelee ennen kaikkea valon, lämpötilan ja biologisen toiminnan voimakas vuodenaikaisuus. Sää vaikuttaa lyhytaikaisesti jokien valumiin ja meren virtauksiin, toisaalta ravinteiden ylimäärä on johtanut vedenlaadun pitkäaikaismuutoksiin ja hitaasti etenevät globaalimuutokset vaikuttavat osin tuntemattomalla tavalla. Saaristomeren vesien dynamiikkaan vaikuttavat lisäksivedenalaiset kynnykset ja saaret, jotka ohjaavat vesien kulkeutumista. Saaristomeri ei siis ole pelkästään saarten, vaan myös altaiden ja vesimassojen mosaiikki, jossa harva veden ominaisuus on pysyvä. Vesien tilan pitkäaikaisseuranta tarjoaa taustatietoa monille tutkimusaloille sekä välttämättömän tietovarannon vesien hoidon ohjaamiseksi. Pitkäaikaismuutosten seuraaminen edellyttää vertailukelpoisia, vuosittain samaan aikaan kerättyjä havaintoja. Lyhyeen vuosittaiseen jaksoon perustuva otanta voi kuitenkin johtaa erilaisiin johtopäätöksiin kuin siinä tapauksessa, että alueita vertailtaisiin niiden koko vuoden kehityksen perusteella. Vuodenaikaiskierrossa voi tapahtua muutoksia mm. ajoituksessa ja vaihteluväleissä, eikä näitä muutoksia pystytä seuraamaan muuten kuin ajallisesti riittävän tiheällä näytteenotolla. Väitöskirjani keskeisin kysymys on, miten yleisimpien meriveden ominaisuuksien vuodenaikaiskierrot vertautuvat alueellisesti. Esimerkiksi pintaveden lämpötilan vuoden kierto toistuu samankaltaisena sijainnista riippumatta, sameuden vuodenkiertoon vaikuttavat puolestaan useat tekijät, joiden merkitys vaihtelee alueittain eri aikoina. Yleistyksien tekemisessä on siis oltava varovainen, kun veden ominaisuuksia kuvaavia havaintotietoja käytetään päätöksenteon tai tutkimuksen taustatietoina. Alueiden luokittelu koko vuodenaikaiskehityksen mukaan on osoittautunut haastavaksi tehtäväksi, sillä se mm. edellyttää useiden, toisiaan alueellisesti ja ajallisesti täydentävien aineistolähteiden käyttöä. Vuodenaikaisvaihteluiden kehityskulkujen alueellinen vertailu avaa kuitenkin uusia näkökulmia rannikkovesitutkimukseen, ja se saattaa auttaa selvittämään Saaristomeren vedenlaatuun vaikuttavien tekijöiden syy-seuraus suhteita.